Using Technology-Based Interventions to Improve the Social-Communication Skills of Adolescents with Autism Spectrum Disorder (ASD) - Anthony, Nicole; Wooten, Cynthia (Journal of the American Academy of Special Education Professionals, 2021)
For more than two decades, researchers have used technology-based interventions to treat symptoms associated with autism spectrum disorder (ASD). Drawing on a preference for technology-driven devices, many advances have been made in the research and treatment of ASD; however, the overwhelming majority of the technology-based interventions are used to address the social-communication challenges of children with ASD under the age of 10 years-old. Thus, the literature review aims to: (a) identify and examine studies that have used technology-based interventions over the past 30 years to improve the social-communication abilities of adolescents with ASD; (b) summarize findings of relevant variables (e.g., participant demographics, experimental setting, and technology-based strategies used to deliver the intervention); and (c) based on reported empirical outcomes, it will be determined, if technology-based interventions are effective in improving the social-communication skills of adolescents with ASD. Results of the current review indicated that technology-based are effective when used to address the social-communication skills of adolescents with ASD. Implications for future research are discussed.